2019
DOI: 10.1186/s13104-019-4516-5
|View full text |Cite
|
Sign up to set email alerts
|

Antibiograms and risk factors of Salmonella isolates from laying hens and eggs in Jimma Town, South Western Ethiopia

Abstract: Objectives Salmonella is the most important causes of foodborne illness especially from poultry and poultry products. So the aim of this study was to carryout phenotypic characterization, antimicrobials susceptibility pattern and risk factors of Salmonella isolates from farms and markets eggs, cloacae swabs of chickens and stool of egg collectors. A cross-sectional study was conducted from January 2018 to September 2018. Samples were, processed; … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
10
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(19 citation statements)
references
References 28 publications
8
10
1
Order By: Relevance
“…In the current study, antibiotic sensitivity and resistance patterns of Salmonella to different antimicrobials are in harmony with previous reports by Islam et al [18]; Ugwu et al [26] and Xie et al [19]. Islam…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…In the current study, antibiotic sensitivity and resistance patterns of Salmonella to different antimicrobials are in harmony with previous reports by Islam et al [18]; Ugwu et al [26] and Xie et al [19]. Islam…”
Section: Discussionsupporting
confidence: 92%
“…The prevalence of Salmonella in egg contents only was 2.22% which was similar to Taddese et al [20] stated that farms egg contents, and market egg contents with 2.4%, and 3.6% Salmonella was prevalent in Jimma Town, Ethiopia. However, the present study was higher than the findings of Karimiazar et al [25] reported that 1.66% of industrial and local egg contents contaminated with Salmonella in Zanjan province, Iran.…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…All (80) Salmonella isolates were found multidrug-resistant. In agreement with this study Salmonella were developed multidrug resistance in Modjo [18], Gondar [7], Jimma [9], and China [8]. This multidrug resistance might be due to the irrational use of antibiotics practiced in the area [26,27] and or evolutionary nature of Salmonella species [16].…”
Section: Discussionsupporting
confidence: 72%
“…Alimentarius are working against antibiotic resistance and set action plans to minimize antibiotic use along the food chain it is increasing at an alarming rate [13,14]. Before this research, many other types of research were conducted to assess the resistance pattern of Salmonella both in human and animals, but due to "evolutionary nature of the bacteria and the dependency of patients to antibiotics", the resistance level of Salmonellae to antibiotics are increasing from time to time [15,16,17,18,6,7,8,9]. Antibiotic resistance surveillance in food animal like sheep is strongly recommended for the mitigation of this global health crisis (AMR) and there was no surveillance has done yet in the study area.…”
Section: Even If the International Tripartite Organizations (Who Faomentioning
confidence: 99%